Commensal Bacteria-Induced Inflammasome Activation in Mouse and Human Macrophages Is Dependent on Potassium Efflux but Does Not Require Phagocytosis or Bacterial Viability - Chen, Kejie (PLoS One, 2016)
Gut commensal bacteria contribute to the pathogenesis of inflammatory bowel disease, in part by activating the inflammasome and inducing secretion of interleukin-1ß (IL-1ß). Although much has been learned about inflammasome activation by bacterial pathogens, little is known about how commensals carry out this process. Accordingly, we investigated the mechanism of inflammasome activation by representative commensal bacteria, the Gram-positive Bifidobacterium longum subspecies infantis and the Gram-negative Bacteroides fragilis. B. infantis and B. fragilis induced IL-1ß secretion by primary mouse bone marrow-derived macrophages after overnight incubation. IL-1ß secretion also occurred in response to heat-killed bacteria and was only partly reduced when phagocytosis was inhibited with cytochalasin D. Similar results were obtained with a wild-type immortalized mouse macrophage cell line but neither B. infantis nor B. fragilis induced IL-1ß secretion in a mouse macrophage line lacking the nucleotide-binding/leucine-rich repeat pyrin domain containing 3 (NLRP3) inflammasome. IL-1ß secretion in response to B. infantis and B. fragilis was significantly reduced when the wild-type macrophage line was treated with inhibitors of potassium efflux, either increased extracellular potassium concentrations or the channel blocker ruthenium red. Both live and heat-killed B. infantis and B. fragilis also induced IL-1ß secretion by human macrophages (differentiated THP-1 cells or primary monocyte-derived macrophages) after 4 hours of infection, and the secretion was inhibited by raised extracellular potassium and ruthenium red but not by cytochalasin D. Taken together, our findings indicate that the commensal bacteria B. infantis and B. fragilis activate the NLRP3 inflammasome in both mouse and human macrophages by a mechanism that involves potassium efflux and that does not require bacterial viability or phagocytosis.